Menelisik Transparansi dan Efektivitas Pengelolaan APBD 2025 untuk Penanganan Banjir di DKI Jakarta - Adelia Rismayani; Laeli Nur Khanifah; Dhiya Fathiyyatul Aulia; Revaldy Putra Razwa (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to evaluate the transparency and effectiveness of the use of the 2025 Regional Revenue and Expenditure Budget (APBD) in flood management in DKI Jakarta Province. Although the provincial government has allocated a large budget, the problem of flooding is still an annual issue that has not been resolved. Using a qualitative case study approach and George C. Edward III's policy implementation theory as an analytical tool, this study examines four key variables: communication, resources, implementer disposition, and bureaucratic structure. The results of the study indicate that policy implementation faces various obstacles such as communication with minimal public participation. Limited technical and human resources, implementer caution due to bureaucratic pressure, and weak integration between agencies. This study concludes that the problem of flooding in Jakarta is not only related to technical aspects, but is also a reflection of the suboptimal regional financial governance and sustainable and accountable public policy implementation system.